2020
DOI: 10.1007/s10584-020-02805-3
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of climate-driven changes on atmospheric, hydrological, and oceanographic variables along the Chilean coastal zone

Abstract: The Chilean coastal zone (CCZ) is subjected to a complex spectrum of anthropogenic, geophysical, biogeochemical, and climate-driven perturbations. Potentially affected variables including atmospheric sea level pressure (Pa), alongshore wind, sea surface temperature (SST), chlorophyll-a, rainfall, river discharge, relative mean sea level (RMSL), and wave climate are studied using in situ and satellite records, hindcasts, and reanalysis datasets. Linear temporal trends and correlations of anomalies are estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 91 publications
(107 reference statements)
3
25
0
Order By: Relevance
“…Periods of marked decrease in runoff levels could be detrimental to anchovy recruitment. Therefore, considering the current reduction of river runoff and freshwater input to the coastal zone in central-south Chile due to climate change and water use for anthropogenic activities (Garreaud et al, 2017(Garreaud et al, , 2019Grez et al, 2020), a decrease in recruitment level of anchovy is likely to occur during years of reduced runoff. Many studies have shown a relationship between freshwater input to the coastal system (through river runoff and/or precipitation) and recruitment variability of neritic fish populations (Quiñones and Montes, 2001;Lloret et al, 2004;Santojanni et al, 2006;Martín et al, 2008;Gillson, 2011;Meynecke et al, 2012).…”
Section: Effect Of Aggregate Runoff (Rivsum) During Anchovy and Commo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Periods of marked decrease in runoff levels could be detrimental to anchovy recruitment. Therefore, considering the current reduction of river runoff and freshwater input to the coastal zone in central-south Chile due to climate change and water use for anthropogenic activities (Garreaud et al, 2017(Garreaud et al, , 2019Grez et al, 2020), a decrease in recruitment level of anchovy is likely to occur during years of reduced runoff. Many studies have shown a relationship between freshwater input to the coastal system (through river runoff and/or precipitation) and recruitment variability of neritic fish populations (Quiñones and Montes, 2001;Lloret et al, 2004;Santojanni et al, 2006;Martín et al, 2008;Gillson, 2011;Meynecke et al, 2012).…”
Section: Effect Of Aggregate Runoff (Rivsum) During Anchovy and Commo...mentioning
confidence: 99%
“…The MegaDrought, 25% of which has been attributed to anthropogenic climate change (Boisier et al, 2016), produced a marked reduction in rainfall/runoff levels in central-south Chile. The reduction in freshwater discharge of major rivers like the Bio-Bio and Itata rivers produced a 25-75% decrease of nitrate and phosphate export to the coastal zone-nutrients which are essential for phytoplankton growth, larval development and feeding of sardine and anchovies (Grez et al, 2020). The high rainfall variability in the study area and climate model uncertainties make it difficult to predict the response of local rainfall to anthropogenic climate forcing (Boisier et al, 2016).…”
Section: Stock Recruitment Models With and Without Runoff As A Covariatementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, local relative SLR can be significantly modulated in coastal regions by vertical ground motions (i.e., subsidence phenomena) either due to natural processes (e.g., global isostatic adjustment, tectonics, sediment consolidation and compaction, and upstream sediment load reduction) [4][5][6][7] or induced/influenced by human activities (e.g., groundwater extraction [8], land reclamation [9], building construction, and consolidation [10]). Ground deformations can be on the same order of magnitude (or greater) than climate-induced SLR [11]. However, in practice, coastal ground motions are often poorly known, and little information is practically available in many cases about the spatial and temporal evolution of ground motion.…”
Section: Introductionmentioning
confidence: 99%
“…Figure11. The tidal anomaly correlation computed from the combination of the four largest tidal constituent amplitudes (given by the detrended sum of the M2 + S2 + K1 + O1) as a proxy for the change in the approximate highest astronomical tide (δ-HAT) relative to detrended MSL in Hong Kong, with the marker size showing the relative magnitude according to the legend, in units of mm m-1.…”
mentioning
confidence: 99%